Effect of maternal hemoglobin and iron status on fetal hemoglobin, iron status, growth and maturity - Kidwai, Mohammad Moaaz; Anand, V. R.; Gulathi, Deepika (International Journal of Contemporary Pediatrics, 2021)
Background: Iron deficiency anemia during pregnancy is a major health issue in India. However, the status of iron stores in infants born to iron depleted mothers remains controversial and inadequately investigated. The present study is therefore an attempt to understand whether maternal anemia and iron stores have any significant effect on iron status and growth of fetus. Methods: This is a prospective, cross-sectional, hospital based study conducted at Mata Chanan Devi Hosital, Janakpuri, New Delhi. Hemoglobin and iron profile of 100 newborns and their mothers were taken. Mothers were divided into anemic and non anemic group to see the effect of maternal anemia on fetus. Results: A total of 100 newborns and their mothers were analysed. Cord hemoglobin and iron profile was significantly reduced in anemic compared to non anemic group. Birth weight of newborn was significantly reduced only in moderately anemic group as compared to non anemic group but there was no difference seen in length and head circumference. Conclusions: Maternal serum ferritin levels should be measured for the diagnosis of occult iron deficiency in the fetus so that timely measures can be taken to prevent iron deficiency anemia in the newborn.